Can incentives improve antipsychotic adherence in major mental illness? A mixed-methods systematic review - Nathan Hodson; Ivo Vlaev; Madiha Majid; Swaran Preet Singh (BMJ Open)
Objectives Incentives have been effectively used in several healthcare contexts. This systematic review aimed to ascertain whether incentives can improve antipsychotic adherence, what ethical and practical issues arise and whether existing evidence resolves these issues.Design Systematic review of MEDLINE, EMBASE and PsycINFO. Searches on 13 January 2021 (no start date) found papers on incentives for antipsychotics. Randomised controlled trials (RCTs), cohort studies, qualitative research and ethical analyses were included. Papers measuring impact on adherence were synthesised, then a typology of ethical and policy issues was compiled, finally the empirical literature was compared with this typology to describe current evidence and identify remaining research questions.Results 26 papers were included. 2 RCTs used contingent financial incentives for long-acting injectable antipsychotic preparations. Over 12 months, there were significantly larger increases in adherence among the intervention groups versus control groups in both RCTs. There were no consistently positive secondary outcomes. 39 ethical and practical issues were identified. 12 of these are amenable to empirical study but have not been researched and for 7 the current evidence is mixed.Conclusions In keeping with other areas of healthcare, antipsychotic adherence can be increased with financial incentives. Payments of 2.5 times minimum wage changed behaviour. The typology of issues reported in this systematic review provides a template for future policy and ethical analysis. The persistence of the effect and the impact of incentives on intrinsic motivation require further research.PROSPERO registration number CRD42020222702.